Ultra-processed food intake and its association with obesity risk factors, Mediterranean diet, and nutrient intake of adults - Alomari, Wajd D.; Almoraie, Noha M. (Frontiers in Nutrition, 2025)
PurposeGrowing awareness highlights ultra-processed food (UPF) as a risk factor for diet-related illnesses. UPF intake is reportedly linked to overweight and obesity statuses; however, this relationship remains unexplored in the Saudi population. In this study, we examined the association between UPF consumption and obesity indicators.MethodsThis study included 190 Saudi participants aged 18–25 years from King Abdulaziz University, Jeddah, Saudi Arabia. Dietary data from two 24-h recalls were classified using the NOVA system. Multiple linear and logistic regression models assessed associations between UPF intake (quartiles) and body mass index (BMI), waist circumference, overweight status (BMI > 25 kg/m2) and abdominal obesity (waist circumference ≥88 cm for females; ≥102 cm for males). Models were adjusted for sociodemographic and lifestyle factors.ResultsUPF consumption was associated with a 30.2% higher BMI, a 23% increase in mean waist circumference, and higher odds of having BMI > 25 kg/m2 and abdominal obesity (OR = 2.966; 95% CI: 1.86, 4.21; OR = 2.610; 95% CI: 1.46, 3.97, respectively). Increased UPF intake correlated with higher BMI, waist circumference, weight, and hip circumference in both sexes.ConclusionHigher UPF consumption is associated with obesity in Saudi adults. Further studies, including intervention trials, are essential to clarify the relationship between UPF intake and health outcomes. Policymakers should promote the consumption of unprocessed or minimally processed foods while limiting UPF intake.